Obacunone Alleviates Inflammatory Pain by Promoting M2 Microglial Polarization and by Activating Nrf2/HO-1 Signaling Pathway - Nan F; Tian Q; Chen S (Dove Medical Press, 2024)
Fubei Nan, Qingxin Tian, Shuangdong Chen Department of Anesthesiology, the First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, People's Republic of ChinaCorrespondence: Shuangdong Chen, Department of Anesthesiology, the First Affiliated Hospital of Wenzhou Medical University, Nanbaixiang Street, Ouhai District, Wenzhou, Zhejiang, 325035, People's Republic of China, Tel +8613732058295, Email wfycshuangd@163.comBackground: Treating inflammatory pain (IP) continues to pose clinical challenge, because of the lack of effective pharmacological interventions. Microglial polarization serves as pivotal determinant in IP progress. Obacunone (OB), a low-molecular-weight compound with a diverse array of biological functions, having reported as an activator of nuclear factor E2-related factor 2 (Nrf2), exhibits anti-inflammatory property. However, it remains uncertain whether OB can alleviate IP by facilitating the transition of microglial polarization from the M1 to M2 state through modulating Nrf2/ heme oxygenase-1 (HO-1) pathway.Methods: We induced an mice IP model by subcutaneously administering Complete Freund's Adjuvant (CFA) into the hind paw. Paw withdrawal latency (PWL) in seconds (s) and paw withdrawal frequency (PWF) were employed to evaluate the establishment of the IP model, while a caliper was used to measure the maximal dorsoventral thickness of the mice paw. Nerve injury was assessed by Hematoxylin-Eosin (HE) Staining. Western blot and got conducted for detection of M1/M2 microglial polarization markers, Nrf2 and HO-1 in spinal cord tissues respectively.Results: In comparison to the control cohort, PWF, M1 phenotype marker iNOS, CD86, paw thickness increased significantly within CFA cohort, while PWL, M2 phenotype marker Arg-1, interleukin-10 (IL-10) decreased in the CFA group. In comparison to model cohort, OB treatment decreased PWF, paw thickness, M1 phenotype marker iNOS, CD86 significantly, while PWL, M2 phenotype marker Arg-1, IL-10, Nrf2, HO-1 increased significantly. The morphological injuries of sciatic nerve in CFA mice were obviously improved by OB treatment. OB inhibited the release of M1-related IL-1β, CXCL1 but promoted M2-related TGF-β, IL-10 in serum in CFA mice. The intervention of the Nrf2 inhibitor ML385 mitigated analgesic effect of OB.Conclusion: We demonstrate that OB is able to attenuate inflammatory pain via promoting microglia polarization from M1 to M2 and enhancing Nrf2/HO-1 signal. OB treatment may be a potential alternative agent in the treatment of IP.Keywords: inflammatory pain, obacunone, Nrf2, HO-1